P0463KIDNEY INVOLVEMENT IN PARAPROTEINEMIC DISEASES - ANALYSIS OF THE SINGLE CENTER REGISTER OF KIDNEY BIOPSIES. (6th June 2020) - Zagorec, Nikola; Šavuk, Ana; Horvatić, Ivica; Kasumović, Dino; Brechelmacher, Ana; Tišljar, Miroslav; Šenjug, Petar; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: Background and Aims: Kidneys are often damaged in paraproteinemic conditions. Paraproteins are monoclonal immunoglobulins or immunoglobulin fractions that are produced by a clonal population of B- or plasma cell lineage and can cause a variety of histological patterns of kidney injury, such as light chain (AL) amyloidosis or light chain cast nephropathy (LCCN). Monoclonal gammopathy of renal significance (MGRS) represents a group of disorders in which a monoclonal immunoglobulin secreted by B- or plasma cell clone causes renal damage. By definition, these disorders do not meet diagnostic criteria for overt, symptomatic multiple myeloma or a lymphoproliferative disorder, but in contrast to monoclonal gammopathy of undetermined significance (MGUS) there is evidence of end-organ damage that can warrant therapy. Method: All patients with paraproteinemic kidney disease were identified by retrospective review of the Hospital Register of kidney biopsies done at Department of Nephrology and Dialysis, in Dubrava University Hospital, Zagreb, from 2009 until 2018. Every kidney biopsy was analyzed by light, immunofluorescent and electron microscopy. Laboratory findings, including serum protein electrophoresis, serum free light chain level and immunofixation of serum proteins, were done for every patient. Clinical and histologic features of patients and features of underlying hematological conditions were analyzed. Results: We identified 47 patients (3, 28% of all biopsies that were done in that period) with kidney disease with clear hematological background. The mean patients' age at the time of the biopsy was 63 years and 27 of them were females. Two patients had signs of direct infiltration of kidneys with malignant lymphomic cells (non-Hodgkin lymphoma) and were excluded from the analysis. Clinical presentation of the patients at the time of biopsy were: proteinuria in 85% of patients, full nephrotic syndrome in 55%, azotemia in 66% of patients (80% had acute kidney injury of unclear etiology) and hematuria in 12, 7%. Most common histologic patterns of kidney injury were AL amyloidosis (45%) and LCCN (30%) but additionally 7 different histological patterns were found: light chain depostion disease, light chain proxymal tubulopathy, fibrillary and imunotactoid glomerulopathy, proliferative glomerulonephritis with monoclonal immunoglobulin deposition, crioglobulinemic glomerulopathy type I and tubulointerstitial damage caused by immunoglobulin deposition. Figure 1 shows main features of patients with AL amyloidosis and cast LCCN. Conclusion: Kidney disease can be initial presentation of an underlying paraproteinemia and, as our data showed, can clinicaly present with acute kidney injury, nephrotic or subnephrotic range proteinuria or full nephrotic syndrome. Variety of histologic patterns of kidney injury were described and AL amyloidosis and LCCN were the most common histological findings. Detailed hematologic workup should follow kidney biopsy in order to determine the exact nature and extension of the disease and therefore the most appropriate therapy.